Rolling Psychodynamic Group for Cocaine Use Disorder: A Single-Group Study Using Multilevel Models. Issue 4 (2nd October 2017) - Pavia, Laura; Tosto, Crispino; Cinquegrana, Antonia; Scioti, Ernesto; Bussola, Tiziana; Cavani, Paola
ABSTRACT: Cocaine disorder has been shown to have an important impact on the success of treatments because it is often associated with social or occupational impairment, high relapse incidences and poor treatment outcomes. Many community group treatment programs for cocaine disorders use a rolling admissions structure, in which a group member who drops out or successfully completes therapy is replaced by another individual. Despite the common use, little is known about the effectiveness of this group. The study involved 18 patients who started a group therapy for cocaine abuse disorder. Outpatients group therapy take place into Clinical Center of Cocaine Addicts in Brescia, Italy. The measures used are DAST-20, OQ-45, GMLCS. The analysis conducted by the Multilevel Models show improvements compared to the symptom that is reliable with respect to psychological functioning. Patients who remain in treatment longer experience a greater quality of relationships within the group.